The use of linked DNA polymorphisms for genotype prediction in families with Duchenne muscular dystrophy. Issue 4 (August 1983) - Harper, P S; O'Brien, T; Murray, J M; Davies, K E; Pearson, P; Williamson, R
Abstract : Two DNA restriction fragment length polymorphisms show genetic linkage to the Duchenne muscular dystrophy locus on the short arm of the X chromosome. Examples are given of families in which these polymorphisms can be used in the prediction of genotype for this disorder.